Carbonic anhydrase II microcrystals suitable for XFEL studies. Issue 6 (5th June 2018) - Lomelino, Carrie L.; Kim, Jin Kyun; Lee, Cheol; Lim, Seon Woo; Andring, Jacob T.; Mahon, Brian P.; Chung, Moses; Kim, Chae Un; McKenna, Robert
Abstract : Carbonic anhydrase II microcrystals suitable for XFEL data collection diffracted to 1.7 Å resolution and were indexed in space group P 21, with unit‐cell parameters a = 42.2, b = 41.2, c = 72.0 Å, β = 104.2°. Abstract : Recent advances in X‐ray free‐electron laser (XFEL) sources have permitted the study of protein dynamics. Femtosecond X‐ray pulses have allowed the visualization of intermediate states in enzyme catalysis. In this study, the growth of carbonic anhydrase II microcrystals (40–80 µm in length) suitable for the collection of XFEL diffraction data at the Pohang Accelerator Laboratory is demonstrated. The crystals diffracted to 1.7 Å resolution and were indexed in space group P 21, with unit‐cell parameters a = 42.2, b = 41.2, c = 72.0 Å, β = 104.2°. These preliminary results provide the necessary framework for time‐resolved experiments to study carbonic anhydrase catalysis at XFEL beamlines.